Pengaruh Kecukupan Modal dan Penyaluran Kredit Terhadap Profitabilitas Dengan Risiko Kredit Sebagai Variabel Pemoderasi Pada Perusahaan Bank Perkreditan Rakyat (BPR) di Malang Raya Periode 2017-2019 - Suati - Rakhmawati; Dwi - Orbaningsih; Oyong Lisa (Program Studi Akuntansi, Fakultas Ekonomi, Universitas Islam Majapahit, 2021)
This research aims to analyze the effect of capital adequacy and lending on profitability with credit risk as a moderating variable. This type of research is associative research with quantitative research methods that are systematic, planned, and structured using numbers as the research approach. The population in this study were 47 rural banks in Malang Raya, while the research sample was selected using a purposive sampling method with certain criteria. Based on the predetermined criteria, there were 28 companies with a three-year research period. The data analysis method used in this research is descriptive statistical analysis, multiple linear regression analysis, and interaction test of Moderated Regression Analysis using the IBM Statistical Package for Social Science version 22nd software. The results of the analysis state that capital adequacy has an effect on profitability, credit distribution has no effect on profitability, credit risk is unable to moderate the relationship between capital adequacy and profitability, and credit risk is unable to moderate the relationship between credit distribution and profitability.